2013
DOI: 10.1111/dme.12228
|View full text |Cite
|
Sign up to set email alerts
|

A randomized crossover study to assess the effect of an oat‐rich diet on glycaemic control, plasma lipids and postprandial glycaemia, inflammation and oxidative stress in Type 2 diabetes

Abstract: AimsIn the UK, lifestyle intervention is first-line management in Type 2 diabetes. It is unclear what type of diet is most efficacious for improving glycaemic control. This study investigated the effects of an oat-enriched diet on glycaemic control, postprandial glycaemia, inflammation and oxidative stress compared with standard dietary advice.MethodsIn a randomized crossover design, 27 volunteers with Type 2 diabetes, managed on diet and lifestyle only, were observed for two consecutive 8-week periods followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 27 publications
1
47
2
1
Order By: Relevance
“…In agreement with data from the main study [43], there were no diet-related effects on glycemic control nor the glycemic or insulinemic responses to the test-meal for the current subpopulation (data not shown). In addition, neither oxidative stress or inflammation were altered between OAT and SDA (data not shown), again in agreement with the larger population [43]. Regression analysis (Table 6) showed that concentrations of total PMP were negatively associated with oxidized LDL (p = 0.041).…”
Section: Mp Regressed Against Other Markerssupporting
confidence: 89%
See 2 more Smart Citations
“…In agreement with data from the main study [43], there were no diet-related effects on glycemic control nor the glycemic or insulinemic responses to the test-meal for the current subpopulation (data not shown). In addition, neither oxidative stress or inflammation were altered between OAT and SDA (data not shown), again in agreement with the larger population [43]. Regression analysis (Table 6) showed that concentrations of total PMP were negatively associated with oxidized LDL (p = 0.041).…”
Section: Mp Regressed Against Other Markerssupporting
confidence: 89%
“…Although both OAT and SDA interventions failed to alter glycemia, inflammation, antioxidant capacity or oxidative stress , there were significant associations between certain of these indices and levels of MP, suggesting that the latter may provide sensitive markers to reflect subtle changes in additional health risks during the early stages of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, it is important to determine the factors that influence the viscosity of b-glucan. Although many in vivo studies (Granfeldt et al 2008;Hlebowicz et al 2008;Charlton et al 2012;Zhang et al 2012;McGeoch et al 2013) have shown a positive influence of b-glucan from oat-incorporated products on health, the magnitude of this effect is variable and sometimes not significant (Lovegrove et al 2000;Chen et al 2006). External influences such as processing of food products prior to digestion might have an impact on the factors that affect b-glucan viscosity and, therefore, may have the potential to influence the physiological effects derived from b-glucan (Tosh et al 2008.…”
mentioning
confidence: 99%
“…External influences such as processing of food products prior to digestion might have an impact on the factors that affect b-glucan viscosity and, therefore, may have the potential to influence the physiological effects derived from b-glucan (Tosh et al 2008. Although many in vivo studies (Granfeldt et al 2008;Hlebowicz et al 2008;Charlton et al 2012;Zhang et al 2012;McGeoch et al 2013) have shown a positive influence of b-glucan from oat-incorporated products on health, the magnitude of this effect is variable and sometimes not significant (Lovegrove et al 2000;Chen et al 2006).…”
mentioning
confidence: 99%